Green aviation industry sustainable development towards an integrated support system. (17th February 2021) - Qiu, Rui; Hou, Shuhua; Chen, Xin; Meng, Zhiyi
Abstract: Sustainable development is becoming increasingly crucial for the green aviation industry. To promote the sustainable development of the green aviation industry, researchers all over the world have attempted to explore and experiment with new initiatives. This study investigates green aviation industry development trends by a bibliometric‐based data analysis system. Cluster, timezone, and timeline visualizations are employed to identify the current development trends of the green aviation industry within three topics: noise, environmental impacts, and green image. In response to environmental challenges, an integrated green aviation industry support system that involves stakeholder engagement should be established, including business strategies, innovative technologies, environmental policies, and public support. In this study, the innovation and sustainability potential of the green aviation industry is evaluated. Then, the roles of strategy improvement, technology integration, policy support, and public participation in forming the integrated support system are examined. The outline of this system may prove helpful for the sustainable development of the green aviation industry.